Kegagalan Konsep Amae dalam Komunikasi Interpersonal Anak Muda di Jepang pada Fenomena Kaeruka Genshou - Zataldi, Novari Ginadya Valentina; Santoso, Budi (KIRYOKU, 2024)
This study aims to describe the failure of amae communication on the social interaction of romantic relationships of youth in Japan in the Kaeruka Genshou phenomenon. The research method used is descriptive qualitative with primary data sources coming from several Youtube documentations related to the Kaeruka Genshou phenomenon. The research object used in this research is interview excerpts regarding the dating experience of young people in Shibuya, Japan. The results showed that the failure of amae in the Kaeruka Genshou phenomenon dominantly caused a sense of disappointment from the amae perpetrator who could not fulfill amae's desires. Meanwhile, excessive attitude also influenced amae's failure a lot. Other factors found were selfishness and shyness in expressing amae's desires.